International perspectives on gender and higher education : student access and success - Fontanini, Christine; Joshi, K. M.; Paivandi, Saeed (Bingley, U.K. : Emerald Publishing Limited, 2020)
Despite improved access to higher education for women, the distribution of women and men varies considerably between different fields of study. The chapters in this edited collection explore the participation status of women in higher education across the varying socio-economic and sociological backgrounds observed in different countries and regions. Diving into the differing social and state intervention policies, individual motives of participation and additional gender inequalities including regional and ethnic disparities, this book offers readers a better understanding of the drivers of gendered trends in higher education, such as the evidently low presence of women in certain scientific and technical disciplines. The analysis focuses on the social construction of gender differences, as well as the roles played by the economy, culture, religion, legal background, and the internal dynamics of society. Ultimately, this book provides a comprehensive overview of recent developments concerning the presence of women in higher education in both developed and developing countries, resulting in a clear picture of the current situation, and how the future might look.
Prelims -- Chapter 1 A Difficult Balance: Policies on Gender Imbalances in the Higher Education Student Population in Flanders -- Chapter 2 Gender in Higher Education: Portuguese Landscape -- Chapter 3 Girls in French Higher Education: Real Progress despite Persistent Inequalities in Scientific and Technological Fields -- Chapter 4 Gender and Higher Education: The Greek Case -- Chapter 5 Italy: Gender Segregation and Higher Education -- Chapter 6 Gender and Higher Education: The Hungarian Case -- Chapter 7 Gender and Higher Education in Spain: A Changing and Hopeful Landscape -- Chapter 8 Girls, Orientation in Science-based Higher Education: The Case of Côte d'Ivoire -- Chapter 9 Feminization of Japanese Higher Education and Career Pathway: From "Interruption" to "Upward Mobility" -- Chapter 10 Women in Higher Education in India: Historical Influences, Contemporary Narratives, and the Way Ahead -- Chapter 11 Feminization of Higher Education in Iran: Paradoxes and Complexities -- Chapter 12 Women's Empowerment through Higher Education: The Case of Bangladesh -- Chapter 13 Women's Access to Brazilian Higher Education: The Case of the Federal University of Santa Catarina -- Chapter 14 Access and Gender Equity in Colombian Higher Education: From Aspirations to Success -- Chapter 15 Women in Canadian Higher Education: The Paradox of Gender Parity and Equity -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Women in higher education; Women -- Education (Higher); Feminism and education; Discrimination in education; Education -- Higher; Higher & further education, tertiary education